ANALISIS PENGARUH E-SERVICE QUALITY, KUALITAS INFORMASI DAN PERSEPSI KEMUDAHAN TERHADAP E-LOYALTY DENGAN E-SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Pada Pelanggan Lazada Indonesia) - Riza, Saiful; Sutopo, Sutopo (Diponegoro Journal of Management, 2017)
This research aim to examine and analyze effect of e-service quality, information quality and ease of use to e-loyalty with e-satisfaction as Intervening variables (Studies on B2C e-commerce Lazada Indonesia customer). This research did through the distribution of questionnaires to 115 Lazada Indonesia customer in Semarang with random sampling method. This research used software SPSS Statistic 22. The technique of data testing in this research includes validity test, reliability test, the classical assumption test, path analysis that is development of multiple linear regression and sobel test to examine mediation effect from independent variabel to dependent variabel.The result of this research indicates that: e-service quality has positive effect and significant to e-satisfaction, information quality has positive effect and significant to e-satisfaction, ease of use has positive effect and significant to e-satisfaction, e-service quality has positive effect and significant to e-loyalty, informationÂ  quality has positive effect and significant to e-loyalty, ease of use has positive effect but not significant to e-loyalty, and e-satisfaction has a positive and significant effect on e-loyalty. The sobel test shows that e-satisfaction can mediate the effect of e-service quality, information quality, ease of use to e-loyalty